Industrial bearings (Virginia : Coastal Video Communications [production company] ; Virginia : Coastal Skills Training [distributor], 1995)
Volume 1 - explain the definition and types of bearings. Volume 2 - explain the installation and care for bearings. Volume 3 - identify the potential problems and determine reasons for failed bearings
no. 1 Application and technology - no. 2 Maintenance and installation - no. 3 Troubleshooting
Copy available in DVD format
Keywords: Bearings (Machinery); Bearings industry